Viability of Crowd funding as an Alternative Funding Mechanism for Youth Entrepreneurs - Salim, Munirah; Kassim, Salina (Human Resource Management Academic Research Society, 2019)
The youth entrepreneurs group is one of the groups who have difficulties in accessing funds and commonly being excluded from the mainstream finance. Youth entrepreneurs face difficulties in accessing financing due to lack of collateral, and lack of credit history, thus being categorised as highly risky borrowers. Due to the technological advancement, crowd funding has emerged as one of the financing alternatives for the youth entrepreneurs to consider. In assessing the viability of crowd funding as a funding alternative, this paper highlights the relationship between perception and types of crowd funding model among youth entrepreneurs in Institusi Pendidikan MARA (IPMA) in considering crowd funding as one of their funding solutions. It further explores what kind of reasons that would increase the interest of youth entrepreneurs in utilizing crowd funding as one of funding solutions. In addition, barriers that keeping youth entrepreneurs from using crowd funding will be identified. Data were collected via questionnaires from youth entrepreneurs at IPMA in Melaka. The results of the study have valuable implications for the relevant authorities particularly on providing a conducive environment to inculcate the entrepreneurial culture and support youth entrepreneurial growth that is in line with the Sustainable Development Goals